2021
DOI: 10.1016/j.virusres.2021.198469
|View full text |Cite
|
Sign up to set email alerts
|

The folate antagonist methotrexate diminishes replication of the coronavirus SARS-CoV-2 and enhances the antiviral efficacy of remdesivir in cell culture models

Abstract: The search for successful therapies of infections with the coronavirus SARS-CoV-2 is ongoing. We tested inhibition of host cell nucleotide synthesis as a promising strategy to decrease the replication of SARS-CoV-2-RNA, thus diminishing the formation of virus progeny. Methotrexate (MTX) is an established drug for cancer therapy and to induce immunosuppression. The drug inhibits dihydrofolate reductase and other enzymes required for the synthesis of nucleotides. Strikingly, the replication of SARS-CoV-2 was inh… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
31
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(32 citation statements)
references
References 63 publications
(71 reference statements)
1
31
0
Order By: Relevance
“…This cell line is very susceptible to viral infection, because it expresses high levels of the SARS‐CoV‐2 receptor ACE2 (Li et al , 2003 ) and is deficient in its interferon response (Emeny & Morgan, 1979 ). For inoculation, we employed a patient‐derived SARS‐CoV‐2 isolate that carries the infection‐enhancing D614G mutation of the Spike (Stegmann et al , 2021 ; preprint: Zhang et al , 2020 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This cell line is very susceptible to viral infection, because it expresses high levels of the SARS‐CoV‐2 receptor ACE2 (Li et al , 2003 ) and is deficient in its interferon response (Emeny & Morgan, 1979 ). For inoculation, we employed a patient‐derived SARS‐CoV‐2 isolate that carries the infection‐enhancing D614G mutation of the Spike (Stegmann et al , 2021 ; preprint: Zhang et al , 2020 ).…”
Section: Resultsmentioning
confidence: 99%
“…Nanobodies were serial‐diluted on a separate 96‐well plate, using supplemented DMEM GlutaMax™ medium (2% FBS). A patient‐derived SARS‐CoV‐2 strain (D614G), which was previously sequenced and described (Stegmann et al , 2021 ) was used for virus infection. Virus stocks corresponding to 2.5 × 10 6 RNA copies of SARS‐CoV‐2 were pre‐incubated with VHH antibodies 1 h prior to infection of cells.…”
Section: Methodsmentioning
confidence: 99%
“…The lung oxidative balance, which is disrupted by MTX administration, may be further disrupted by COVID-19-based oxidative stress. Although there are no studies in the literature linking lung tissue damage caused by COVID-19 and MTX, the new preclinical evaluation of MTX for the treatment of COVID-19 has not been successful (Stegmann et al, 2021). SARS CoV-2 uses the human angiotensin I converting enzyme 2 (ACE2) for entry into the cells with its spike protein.…”
Section: Discussionmentioning
confidence: 99%
“…Stegman et al revealed that SARS CoV-2 replication was inhibited by MTX in therapeutic concentrations of 1 μM, which led to a more than a 1000-fold decrease in virus progeny in Vero C1008 cells and Calu3 cells. They also stated that the inhibitory effect of MTX was primarily based on reduced purine synthesis(Stegmann et al, 2021). When whey protein was used as an inhibitor of furin activity and lung of group C + W was used as a source of furin, inhibition of furin was higher in the lung of group C + W compared with the C group.…”
mentioning
confidence: 99%
“…Remdesivir in combination with methotrexate (MTX) led to synergistic impairment of the replication of SARS-CoV-2 as MTX improves remdesivir efficacy in treated Vero cells by reducing the RNA virus in the cell supernatant by more than 98% while each drug alone reduces the RNA virus by 50%–75% ( 81 ).…”
Section: Remdesivir Combined With Repurposed Drugsmentioning
confidence: 99%